Structural diversity and phylogenomic insights from the mitochondrial genomes of two populus species from the Qinghai-Tibet Plateau - Huang, Jin-Liang; Shi, Yu-Jie; Tian, Fei-Fei; Mi, Jia-Xuan; Zhang, Fan; Zhou, Shi-Xing; Wan, Xue-Qin; Huang, Cong-De (Frontiers in Plant Science, 2025)
Populus kangdingensis and P. ciliata are important tree species distributed across the Qinghai–Tibet Plateau, yet the structure and evolutionary characteristics of their mitochondrial genomes remain unclear. To elucidate these features and their phylogenetic relationships, we assembled the mitochondrial genomes of these two species using PacBio HiFi sequencing data with PMAT2, and annotated them with PMGA. The results showed that the mitochondrial genome of P. kangdingensis consists of three independent circular molecules with a total length of 785,824 bp, while that of P. ciliata exhibits a branched structure comprising two circular molecules and one linear molecule, totaling 798,807 bp. Both genomes contain 57 functional genes, including 34 highly conserved protein-coding genes. Comparative genomic analyses revealed differences in repeat sequences, RNA editing patterns, and chloroplast-derived sequences, suggesting species-specific evolution at the organellar genome level. Ka/Ks analysis identified genes such as atp4, ccmB, and mttB as potentially under positive selection, reflecting adaptation to high-altitude environments. Phylogenetic trees constructed using 30 mitochondrial and 58 chloroplast protein-coding genes confirmed the monophyly of Populus and Salix, and identified them as sister groups. However, topological inconsistencies observed within Populus suggest the influence of lineage sorting, hybridization, and differences in mutation rates. This study provides the first high-quality mitochondrial genomes of P. kangdingensis and P. ciliata, revealing the structural diversity of multi-circular and branched conformations in Populus mitochondrial genomes, and offering new insights into organellar genome evolution and high-altitude adaptation in this genus.